Permainan Puzzle Menggunakan Media Gadged Menurunkan Kecemasan Anak Yang Akan Sirkumsisi - Reski, Sisilia Sri; Yunita Sari, Ignasia; Haryanti, Priyani; Prawesti, Indah (Health Information : Jurnal Penelitian, 2021)
Anxiety experienced by children who will be circumcised is an anticipatory response to new experiences that are considered a threat in themselves. Strategies are needed to reduce anxiety and the impact of trauma on anxiety. The purpose of this study was to determine the effect of puzzle games using gadgets on the anxiety level of children who will be circumcised at the Jogja Circumcision House RH Medika Yogyakarta. The method used is a pre-experimental one group pretest-posttest group design. The sampling technique used is quota sampling as much as 30. Data analysis using the Wilcoxon test. The results of the study. The level of anxiety before the puzzle game using gadgets was mostly in the moderate category (76.7%) and after in the mild category (66.7%). The Wilcoxon test results obtained a p value of 0.000 (P value <0.05), which means that there is an influence of puzzle games using gadgets on the anxiety level of children who will be circumcised at the Jogja Circumcision House RH Medika Yogyakarta.